Pendidikan Karakter Berbasis Kearifan Lokal: Kajian Filosofis Tradisi Rokat Pandaba untuk Mengurangi Perilaku Ghasab di Pondok Pesantren - Mahtumah Al Harie; Mudafiatun Isriyah; Weni Kurnia Rahmawati (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Ghasab, the act of using another person’s belongings without permission, remains common in Islamic boarding schools. The problem is far from trivial because it conflicts with religious norms while eroding the trustworthy character (amanah) of students. Responses have so far relied on advice, reprimands, and sanctions, yet they have done little to change behaviour because they rarely reach inner awareness. This article examines the philosophical values embedded in the Rokat Pandaba tradition and considers whether they can serve as a cultural approach to curbing ghasab. The study uses a Systematic Literature Review of sources from Google Scholar, Garuda, and DOAJ published between 2013 and 2026. The review identifies five core values within Rokat Pandaba: self-reflection (muhasabah), inner purification, asking forgiveness, moral responsibility, and the resolve to change. These values resonate with Kohlberg’s theory of moral development, Lickona’s character education, and the multicultural counselling framework of Sue and Sue. The findings indicate that integrating local wisdom such as Rokat Pandaba into character education in pesantren may offer a more grounded approach, both educationally and therapeutically, for addressing ghasab.